2018
DOI: 10.1038/s41419-017-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA GRB10 as a competitive endogenous RNA regulating nucleus pulposus cells death in degenerative intervertebral disk

Abstract: Intervertebral disc degeneration (IDD) is an important factor leading to low back pain, but the underlying mechanisms remain poorly understood. Compared with normal nucleus pulposus (NP) tissues, the expression of circ-GRB10 was downregulated in IDD. Furthermore, overexpression of circ-GRB10 inhibited NP cell apoptosis. circ-GRB10 could sequester miR-328-5p, which could potentially lead to the upregulation of target genes related to cell proliferation via the ErbB pathway. In conclusion, the present study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 53 publications
1
81
0
Order By: Relevance
“…38 Recently, it has been reported that specific circRNAs have been identified as significant regulators and biomarkers for degenerative disc disease. 39-42 The underlying mechanism mostly relies on their abilities to counteract the inhibitory effects of miRNAs on the target genes. Due to the development of microarray profiling, bioinformatic approaches and sequencing techniques, the identification of novel circRNAs as effective regulatory factors and potential therapeutic targets for IDD is expected.…”
Section: Discussionmentioning
confidence: 99%
“…38 Recently, it has been reported that specific circRNAs have been identified as significant regulators and biomarkers for degenerative disc disease. 39-42 The underlying mechanism mostly relies on their abilities to counteract the inhibitory effects of miRNAs on the target genes. Due to the development of microarray profiling, bioinformatic approaches and sequencing techniques, the identification of novel circRNAs as effective regulatory factors and potential therapeutic targets for IDD is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, reduced circ‐GRB10 levels were found to increase the availability of miR‐328‐5p and thereby repressing ERBB2 (v‐erb‐b2 erythroblastic leukaemia viral oncogene homolog 2; a target of miR‐328‐5p). These data suggested that deregulation of circ‐GRB10/miR‐328‐5p/ERBB2 pathway was involved in IDD development . Restoring the expression of circ‐GRB10 or enhancing the ERBB2 signalling might thus serve a new therapeutic approach for the IDD.…”
Section: Functional Roles Of Specific Circrnas In Iddmentioning
confidence: 93%
“…and miR-328-5p were one of the most significantly negatively correlated circRNA-miRNA pairs 44. By RT-qPCR, the investigators verified the significant downregulation of circ-GRB10 and upregulation of miR-328-5p as well as their negative correlation in an independent set of IDD NP samples.…”
mentioning
confidence: 83%
See 2 more Smart Citations